Agent-Based Control Framework for Distributed Energy Resources Microgrids - Jiang, Zhenhua (2006 IEEE/WIC/ACM International Conference on Intelligent Agent Technology : proceedings : 18-22 December, 2006, Hong Kong, China, 2006)
Distributed energy resources (DERs) provide many benefits for the electricity users and utilities. However, the electricity distribution system traditionally was not designed to accommodate active power generation and storage at the distribution level. The microgrid provides an effective approach to integrating many small-scale distributed energy resources into the bulk electric grid. This paper presents an agent-based control framework for distributed energy resources microgrids. The features of agent technology are first discussed. An agent-based control framework for DER microgrids is then presented. To demonstrate the effectiveness of the proposed agent-based control framework, simulation studies have been performed on a dc distributed energy system that can be used in a microgrid as a modular power generation unit. Simulation results clearly indicate that the agent-based control framework is effective to coordinate the various distributed energy resources and manage the power and voltage profiles.